Language Regression in Childhood Autism - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The clinical characteristics of 177 children (82% male and 18% female) with language regression were identified and studied prospectively at four medical centers: Montefiore and Albert Einstein, New York, NY; St Louis Children's, MO; Miami Children's, FL; and Yale University, CT.